SCHOOL READINESS IN DEALING POST-COVID-19 PANDEMIC CONDITION AT JUNIOR HIGH SCHOOLS IN BATUDA GORONTALO - Deviyanti, Seklin Nova; Sumar, Warni Tune; Lamatenggo, Nina (International Research-Based Education Journal, 2022)
This research is about school readiness in dealing with the post-covid-19 pandemic in junior high schools in Batudaa sub-district, Gorontalo district which aims to determine: (1) School readiness in managing health services, (2) School readiness in managing facilities and infrastructure, (3) School readiness in post-pandemic learning, and (4) School readiness in human resource management. This research method uses a quantitative approach with the type of research that is descriptive explanatory. Data collection techniques using questionnaires (questionnaires), interviews, and documentation. Data analysis techniques used are descriptive analysis techniques using percentage formulations. The results showed that: (1) School readiness in managing health services was in the ready category, (2) school readiness in managing facilities and infrastructure in the fairly ready category, (3) School readiness in learning management was in the ready category, (4) School readiness in human resource management is in the fairly ready category. For this reason, it is recommended: (1) Principals are expected to improve school readiness in managing health services and managing facilities and infrastructure in order to meet health protocol standards for face-to-face teaching and learning, (2) Educators and education staff are expected to be more creative and innovative in developing learning good post-pandemic, (3) Educators and education staff are expected to improve their abilities in the fields of technology, information and communication to be better prepared in good teaching and learning activities in the digital era, (4) Other researchers are expected to deepen this research, especially on aspects -aspects that have not been studied by researchers